The effects of warm-up duration on cycling time trial performance in trained cyclists - Bunn, J. A.; Eschbach, C.; Magal, M.; Wells, E. K. (Central European Journal of Sport Sciences and Medicine, 2017)
The purpose of this study was to assess the effects of three different warm-up condi-tions on a 5K cycling time trial (TT). Sixteen trained cyclists completed the study. At the first testing session, participants completed a maximal graded exercise test to assess maximal oxygen consumption (VO2max) and a familiarization of the TT. At three subse-quent visits, the participants completed the TT after no warm up, short warm-up of three minutes at 60% VO2max, or long warm-up of ten minutes at 60% VO2max. The warm-up was assigned in randomized order. VO2, heart rate (HR), lactate, power, and speed were assessed after the warm-up, 1K, and completion of the 5K TT. There was no dif-ference between type of warm-up for time, power, cadence, speed, VO2, HR, or lactate levels at the end of the TT. There was no significant difference between type of warm-up for time, VO2 or HR at the end of the 1K split. Warm-up length was not impactful on 5K TT performance or during the first km of the TT in trained cyclists. These results con-flict with previous evidence indicating that a warm-up in endurance events primarily improved VO2 kinetics at the onset of the exercise.